Safety and efficacy of transarterial chemoembolization in patients with transjugular intrahepatic portosystemic shunts. Issue 8 (August 2015) - Miura, John T.; Rilling, William S.; White, Sarah B.; Hieb, Robert A.; Tutton, Sean M.; Patel, Parag J.; Gamblin, T. Clark; Hohenwalter, Eric J.
Abstract Background Transarterial chemoembolization (TACE) for the treatment of hepatocellular carcinoma (HCC) is an important option as the majority of patients present with advanced disease. Data regarding treatment outcomes in patients who have undergone transjugular intrahepatic portosystemic shunts (TIPS) are limited. The present study seeks to evaluate the safety and efficacy of TACE in HCC patients with a TIPS. Methods A retrospective review identifying patients with HCC and concomitant TIPS who were treated with TACE was performed. Results From 1999 to 2014, 16 patients with HCC underwent a total of 27 TACE procedures; eight patients required multiple treatments. The median patient age at the time of the initial TACE was 60.5 years [interquartile range (IQR) : 52.5–67.5] with the majority being male (n = 12, 75%) and Childs–Pugh Class B (n = 12, 75%). At 6 weeks after TACE, 56.3% of patients achieved an objective response rate (complete and partial response) by mRECIST criteria. Clavien Grade 3 or higher complications occurred in 11.1% of TACE procedures. There were no peri‐procedural deaths. The median progression‐free (PFS) and overall survival (OS) were 9 and 22 months, respectively, when censored for liver transplantation (median follow‐up: 11.5 months). Conclusion TACE is an effective treatment strategy for HCC in TIPS patients; albeit may be associated with higher complication rates.